ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI PEGADAIAN DIGITAL SERVICE DI PT. PEGADAIAN UNIT PANAIKANG MAKASSAR - Mointi, Renny; Nurfadilah, Nurfadilah; Madrianah, Madrianah; Pratiwi Ar, Dhita; Rusli, Rusli (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2023)
In the business world, especially banking and non-banking, it has been very advanced, in order to remain on the stage of business competition, these institutions have made many technological innovations in their companies in order to provide the best facilities to customers so that they feel satisfied and remain loyal in the company. Customer satisfaction is one of the most important factors because it involves a person's feelings of pleasure or disappointment that arise after comparing perceptions or impressions of the performance or results of a product and its expectations. This study aims to analyze the level of user satisfaction with the digital service pawnshop application at PT. Pegadaian Unit Panaikang Makassar. The method used is gap analysis using the SPSS V. 20 program. 20. The data was tested with validity and reliability tests using SPSS V.20. The data obtained is valid because the significant value of each statement item is> 0.20, while the resulting data reliability test is> 0.6 with a performance of 0.642, and expectations of 0.691, so the research instrument is declared reliable. The research results obtained by the author show that the user satisfaction of the Pegadaian Digital Service application is very satisfying because> 69.